Open Education and Alternative Digital Credentials in Europe - Griffiths, Dai; Burgos, Daniel; Aceto, Stefania (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
Learners who learn from OER often cannot have their learning assessed or receive a credential. Open credentials offer a potential solution to this problem, combining badges or micro-credentials with competence frameworks and digital seals. This study identified the current situation of open credentials in post-secondary education in Europe, the main themes of the discourse, and the points of agreement and divergence surrounding them. The data comprised a corpus of transcriptions from 12 expert interviews and a focus group. Qualitative text analysis identified the principal themes. Findings included the following: (a) few assessments are available as open content; (b) linking OER and credentials requires detailed and expensive work on learning outcomes and assessment; (c) the aggregation of open credentials to create higher-level qualifications is a widely accepted ambition; (d) the European Union’s infrastructure to support open credentials is appropriate and effective and can foster trust; (e) the outstanding challenges are organisational and practical, not technological; (f) assessment and content provisions should belong to separate organisational functions; and finally, (g) funding and support for open credentials in professional accreditation are essential for further progress.